Optimization of Process for Enzymatic Resolution of Racemic Amines using Continuous Flow Bioreactor - Meyer, Elazar (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The optimization of enzymatic process for the resolution of chemically and pharmaceutically important racemic amines is described using a continuous flow bioreactor. Also described are the isolation and purification methods of the reaction products and the various parameters affecting the optimal reaction conditions for the enzymatic resolution to afford the products in high chemical purity and enantiomeric excess (ee) of over 90%.